On the Forecasting of Nor'westers in Gangetic West Bengal (MAUSAM, 1957)
A comparative study has been made of the upper air data based on radiosonde ascents at Calcutta and Allahabad, in relation to two distinct classes of days, namely, those of wide spread nor'westers of the pre-monsoon season over Gangetic West Bengal and those altogether free from such storms. It is seen that the most important contributory factors to the genesis of well developed nor westers are, increased humidity resulting in suitable distribution of wet bulb temperatures m the first two kilometres and cyclonic convergence in the lower moist air field to provide the initial impulse for upward convection, and that the advection of colder air at higher levels is not an essential criterion.A nomogram using dry bulb and dew point temperature values at 850-mb level in the morning has been suggested to serve as an empirical, but quite a useful, tool for the forecasting of nor'westers over Gangetic West Bengal during the pre-monsoon season.